DINAMIKA KELOMPOK TANI SASARAN PROGRAM UPAYA KHUSUS PENINGKATAN PRODUKSI PADI PADA DAERAH SENTRA PRODUKSI PADI DI KABUPATEN MANOKWARI (STUDI KASUS KAMPUNG PRAFI MULYA DISTRIK PRAFI) - Triman Tapi (JURNAL TRITON, 2016)
The purpose of research is to describe the dynamics of the target farmer groups Special Effort program (Upsus) to increase rice production in the area of rice production centers in the district of Manokwari. The benefits of this research are expected to provide information to stakeholders in order to develop and development of farmer groups as targets of the program of activities. The study lasted for two months, starting from November to December 2015. The research was conducted in the village of Prafi Mulya, District Prafi, Manokwari regency, with the method of data analysis done tabulation and descriptive qualitative analysis. The results showed that the dynamics of farmer groups included in the category of Medium or quite dynamic, and Upsus program to increase rice production in 2015 has contributed to pushing the process dynamics in the group.